2015
DOI: 10.1530/rep-14-0524
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in follicle development and oocyte competence

Abstract: Apart from its well-known role in regulating endothelial function, in mammals, nitric oxide (NO) is an important signaling molecule involved in many processes, regulating different biological functions. It has been demonstrated that NO plays a role in the physiology of the reproductive system, where it acts in controlling the activity of reproductive organs in both sexes. In the female of several animal species, experimental data suggest the presence of an intraovarian NO-generating system, which could be invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 109 publications
0
37
0
Order By: Relevance
“…Follicular oocytes are capable of generating nitric oxide (NO) sufficient to modulate oocyte physiology (Kuo et al . ; Basini & Grasselli ; Thompson et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Follicular oocytes are capable of generating nitric oxide (NO) sufficient to modulate oocyte physiology (Kuo et al . ; Basini & Grasselli ; Thompson et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary gonadotropins modulate expressions of various nitric oxide synthase (NOS) isoforms. 40 Both pregnant mare's serum gonadotropin (PMSG) and hCG have been shown to influence inducible nitric oxide synthase (iNOS) expressions in rat ovary. 41 Recent studies from our laboratory suggest that decreased level of nitric oxide (NO) is associated with meiotic exit from diplotene, as well as M-II arrest, 12 , 17 , 22 while high level of NO induces cell cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…A moderate increase of intracellular Ca 2+ ([Ca 2+ ]i) level under the physiological range triggers generation of ROS and decreases iNOS expression during spontaneous EDA in rat oocytes cultured in vitro [14,22,[46][47][48]. Our results suggested that increase of ROS level and decrease of iNOS expression induced EDA after 7 h of in vitro culture.…”
Section: Rosmentioning
confidence: 64%